Implementing Equal Living Conditions in a Federation - Andreas Wagener (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1998)
Critical-level (CL) utilitarianism with both fixed and variable critical levels is applied to the problem of redistribution in a federation with free mobility. We are interested in intra-regional inequality when redistribution policies are organized decentrally in a federation. Due to free mobility, this topic cannot be analysed independently of normative issues of variable population sizes. In our two-region model, the recipients of welfare payments are two classes of mobile "poor" workers, whereas the contributors to the welfare system are immobile. Regional governments are CL utilitarians and behave non-cooperatively. Under autarky, CL utilitarians implement an egalitarian solution. With free mobility, some degree of intra-regional inequality proves to be optimal in general. However, a full equalization within and across regions can be reached as a Nash equilibrium if and only if regional governments regard the immigration of average income earners as welfare neutral - which is shown to be normatively unattractive.
Keywords: H71; D63; 330